Analysis of the rentability of the sunflower production system: Non irrigated or irrigated - Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Although it is still argued that crop irrigation brings higher yields and higher incomes, it does not always take into account the costs of these additional works. Thus, there may be some cases where the level of these expenditures exceeds the productivity gain, and therefore there is a disadvantage (loss). The question that arises from this context is the following: is it worth to irrigate the sunflower culture in order to increase yield? In order to determine the efficiency (profitability) of the two crop systems (irrigated and non-irrigated) data from ADER 13.1.2 will be used to calculate the economic indicators in order to determine the level of profitability between the two systems. These data will refer to crop technology and the income and expenditure budget for setting up and operating a hectare of sunflower.
Keywords: Q12; Q15; 330; irrigation; non-irrigation; sunflower; profitability